Emotional Androgyny: A Preventive Factor of Psychosocial Risks at Work? - Gartzia, Leire; Pizarro, Jon; Baniandres, Josune (Frontiers in Psychology, 2018)
Although previous studies have acknowledged the connections between gender and emotional competences, more research is needed on how gender and emotion interact to influence psychosocial risks at work. This paper addresses how gender stereotypes and emotions simultaneously act as psychosocial antecedents of organizational stress. Following the principles of psychological androgyny, we propose that a combination of communion and agency can serve as a preventive factor at work and lead to healthier responses by providing a wider range of emotional competences to deal with organizational demands. Following previous methodological approaches, we include a quantitative review about scientific research on occupational health in the PsycINFO database during the period 1980–2017 from a multidimensional gender perspective that differentiates between studies addressing the topic from either sex, gender or gender identity dimensions. Finally, we propose new analytical directions to deal with psychosocial hazards at work by underscoring some of the complex ways in which gender and emotional competences influence psychosocial risks at work.